Effects of Normoxic Recovery on Intima-Media Thickness of Aorta and Pulmonary Artery Following Intermittent Hypoxia in Mice - Umeda, Akira; Miyagawa, Kazuya; Mochida, Atsumi; Takeda, Hiroshi; Takeda, Kotaro; Okada, Yasumasa; Gozal, David (Frontiers in Physiology, 2020)
Obstructive sleep apnea (OSA) patients are at risk for increased blood pressure and carotid intima-media thickness (IMT), with pulmonary hypertension and right-sided heart failure potentially developing as well. Chronic intermittent hypoxia (IH) has been used as an OSA model in animals, but its effects on vascular beds have not been evaluated using objective unbiased tools. Previously published and current experimental data in mice exposed to IH were evaluated for IMT in aorta and pulmonary artery (PA) after IH with or without normoxic recovery using software for meta-analysis, Review Manager 5. Because IMT data reports on PA were extremely scarce, atherosclerotic area percentage from lumen data was also evaluated. IH significantly increased IMT parameters in both aorta and PA as illustrated by Forest plots (P < 0.01), which also confirmed that IMT values after normoxic recovery were within the normal range in both vascular beds. One-sided scarce lower areas in Funnel Plots were seen for both aorta and PA indicating the likelihood of significant publication bias. Forest and Funnel plots, which provide unbiased assessments of published and current data, suggest that IH exposures may induce IMT thickening that may be reversed by normoxic recovery in both aorta and PA. In light of the potential likelihood of publication bias, future studies are needed to confirm or refute the findings. In conclusion, OSA may induce IMT thickening (e.g., aorta and/or PA), but the treatment (e.g., nasal continuous positive airway pressure) will likely lead to improvements in such findings.